Customer Engagement: Eksplorasi Customer Relationship Management dan Media Sosial di UMKM - Vanessa Gaffar; Tika Annisa Koeswandi; Annisa Ciptagustia (Universitas Winaya Mukti, 2023)
This study aims to explore how Customer Relationship Management (CRM) and Social Media affect to Customer Engagement at the MSMEs in the city of Bandung. This study used a descriptive-quantitative approach involving 336 SMEs in the city of Bandung. Data were collected through questionnaires and literature studies. Data were analyzed using path analysis where variable (X1) was CRM, social media was variable (X2) and variable (y) was Customer Engagement. The results of this study indicate that there is a strong relationship between CRM and Social Media. The direction of the relationship is positive which shows a unidirectional relationship pattern, which means that when there is an increase in CRM it will be followed by an increase in Social Media, and vice versa. Based on the test results it can also be concluded that CRM and Social Media have a significant effect on Customer Engagement, both jointly and partially. The suggestions for further research are to examine whether customer engagement can affect customer loyalty, especially to the consumers in today's digital era.